Antiwar in Black Sabbath’’s Lyrics of Song “War Pigs” - Handoko, Putut (Faculty of Letters, Dr. Soetomo University, 2017)
Relief that decorates temples in East Java in the form of ornament of the story of animal beautifies the temples and it has meaning and important role. The research of the relief of animal story focuses on determining the role and kinds of animal in the relief of story animal of temples in East Java.The aim of this research is to spread the meaning relief of animal story of Temple in East Java in the form of the role and the kinds of animal of the relief of the story of animal.The technique of data collection is documentation study, observation and interview.The finding shows that the animal story in the relief of the animal story of Jago temple in Malang functions as a means of spreading religion and offers moral ethic message and moral for human, through the symbols demonstrated with the figure of animal. The types of animal in the relief of the story of animal are flamingo, turtles and wolfs.The story of Garudeya in the relief of the animal story of Kidal temple in Malang functions to offers a moral message of the release of soul for freedom from physical bond and a danger that close up after the death. The types of animal in the relief of the animal story are Eagle and snakes. The story of animal in the relief of the story of animal of Penataran temple in Blitar functions to offer a message of ethich moral, the value of mutual help, the value of friendship, the value of showing gratitude. The types of animal in the relief of the animal story are Swan. turtles, dogs, crocodile and cows. Keywords : Relief, Temple, relief of the story animal